Dynamic synthetic inertial control method of wind turbines considering fatigue load - Wang, Hanbo; Liu, Yingming; Wang, Xiaodong; Guo, Guoxian; Wang, Liming (Frontiers in Energy Research, 2023)
This paper proposes a dynamic synthetic inertia control method, considering the fatigue loads of the wind turbine. The control objectives include reducing the rate of change of frequency and frequency nadir of the power system and the fatigue load of the shaft and tower of the wind turbine. A frequency regulation model of the power system containing the primary operating dynamics of the wind turbine is established. The dynamic synthetic inertia control method is proposed according to the relationship between fatigue load, wind velocity, and frequency. Case studies are conducted with a wind turbine fatigue load under a synthetic inertia control with different weights for different wind velocities and system loads. Therefore, the dynamic weights are obtained. Comparing the rate of change of frequency and frequency nadir and equivalent damage load, the efficacy of the proposed method is verified.